VERIFIKASI DATA PARTAI POLITIK PESERTA PEMILU PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 55/PUU-XVIII/2020 - Frendi Sabil; Reni Dwi Purnomowati (Reformasi Hukum Trisakti, 2023)
The Constitution of the State is the foundation or basis for the establishment of a State. However, in practice, the fulfillment of election activities has several processes, one of which is party data verification which is used as a prerequisite for political parties to participate in the implementation of elections. The problem is whether the Elimination of Factual Data Verification of Political Parties Parliamentary Threesholds in KPU regulation No. 6 of 2018 is in accordance with Election Law No. 7 of 2017. This research method is normative. The nature of this research is analytical descriptive. The method of drawing conclusions is deductive logic. With qualitative data processing. The results of this research and discussion refer to the Election Law Number 7 of 2017 to discuss this research. The conclusion of the research is KPU Regulation Number 6 of 2018 regarding verification.